The PERCEPTIONS OF SECONDARY SCHOOL STUDENTS ON AGRICULTURE AS A CAREER CHOICE IN AKOKO SOUTH-WEST LOCAL GOVERNMENT AREA, ONDO STATE, NIGERIA - Oluwatoyin Bukola Chete; Blessing Felicia Oniye (Agricultura)
This study assessed the perceptions of secondary school students of agriculture as a career choice in Akoko LGA, Ondo State, Nigeria. A two-stage sampling technique was used to select 120 respondents. Descriptive and inferential statistics were used to analyse data from a structured questionnaire. Respondents were mostly female (60.8%), Christian (72.5%), members of small households and sponsored by parents (90.8%). The perceptions results showed that “peer groups believe agriculture is for low-achieving students” had the highest mean score (x̅=3.96; σ=1.32). The most favourable attitude statement was "I would recommend studying agricultural science to others" (x̅=4.06; σ=4.77), The most serious constraints was insufficient time allotted for agricultural practical sessions (x̅= 2.26; σ=1.08). The most cited way of making agriculture attractive and accepted by students was through curriculum enhancement (x̅= 4.76; σ=0.95). The study recommended that schools should incorporate practical agriculture to spark interest and hands-on learning of the subject.